Genetic heterogeneity within the HLA region in three distinct clinical subgroups of myasthenia gravis - Saruhan-Direskeneli, Güher; Marx, Alexander (Clinical immunology, 2016)
This study aims to investigate genetic susceptibility to early-onset and late-onset anti-acetylcholine receptor antibody positive myasthenia gravis (EOMG and LOMG) and anti-muscle specific kinase antibody positive MG (MuSK-MG) at genome-wide level in a single population. Using a custom-designed array and imputing additional variants and the classical HLA alleles in 398 patients, we detected distinct associations. In EOMG, rs113519545 in the HLA class I region (OR=5.71 [3.77-8.66], P=2.24x10-16), HLA-B*08:01 (OR=7.04 [3.95-12.52], P=3.34x10-11) and HLA-C*07:01 (OR=2.74 [1.97-3.81], P=2.07-9), in LOMG, rs111256513 in the HLA class II region (OR=2.22 [1.59-3.09], P=2.48x10-6) and in MuSK-MG, an intronic variant within HLA-DQB1 (rs68081734, OR=5.86, P=2.25x10-14) and HLA-DQB1*05:02 (OR=8.56, P=6.88x10-13) revealed the most significant associations for genome-wide significance. Differential genetic susceptibility within the HLA to EOMG, LOMG and MuSK-MG has been established in a population from Turkey.